The bitter fruits of martyrdom. About Brandimarte’s death (“Orlando furioso” XLI-XLIII) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2021)
The essay retraces the evolution of Brandimarte, a character invented by Boiardo, focusing especially on the episode of his death in the Furioso (XLI-XLIII). If it is true (as shown by Monteverdi, Quint, and others) that in Lipadusa’s episode Ariosto immolates Orlando’s faithful friend to the triumph of an epos shaped by Roncesvalles’ sacrifice, neverthless, the union between the political and courtly ethos with which Boiardo substantiates his character slightly but symptomatically reappears also in the Furioso. Accordingly, the Christian martyrdom to which the character is finally (and ambiguously) destined by Ariosto seems on a closer inspection to be contradicted, if not retracted, by other episodes in the same poem. Finally, a comparison is proposed between the death (and in particular the funeral) of the young Brandimarte and that of Gaston de Foix, the french captain whose death in Ravenna’s battle in 1512 deeply moved his contemporaries.
Keywords: Ariosto; Orlando furioso; Boiardo; Brandimarte; christian martyrdom; Gaston de Foix